Dynamic surface tension of aqueous solutions of ionic surfactants: Role of electrostatics - Ritacco, Hernán Alejandro (2011)
The adsorption kinetics of the cationic surfactant dodecyltrimethylammonium bromide at the air-water interface has been studied by the maximum bubble pressure method at concentrations below the critical micellar concentration. At short times, the adsorption is diffusion-limited. At longer times, the surface tension shows an intermediate plateau and can no longer be accounted for by a diffusion-limited process. Instead, adsorption appears kinetically controlled and slowed down by an adsorption barrier. A Poisson-Boltzmann theory for the electrostatic repulsion from the surface does not fully account for the observed potential barrier. The possibility of a surface phase transition is expected from the fitted isotherms but has not been observed by Brewster angle microscopy. © 2011 American Chemical Society.